Kobiety w literackiej przestrzeni „rosyjskiego Izraela” - Lenart, Agnieszka (Rusycystyczne Studia Literaturoznawcze, 2017)
This article discusses the role of women in the life of „Russian-speaking Israel”. The author gives the names of outstanding women — writers, poets, literary critics, representatives of Russian aliyah in Israel, the seventies and nineties. Among them are: Dora Shturman, Lydia Yanovska, Nina Voronel, Elena Axelrod, Maya Kaganskaya. It turns out that women are a significant part of the cultural space of Israel and the Russian literature of emigration.